Mixed grain boundary diffusion source for sintering NdFeB magnet and preparation method and application of mixed grain boundary diffusion source
By preparing and optimizing the process of mixed grain boundary diffusion sources, the challenges of corrosion resistance and coercivity of NdFeB permanent magnet materials have been solved, achieving efficient utilization of rare earth elements and improved diffusion effect, which is suitable for new energy vehicles and wind power generation.
Patent Information
- Application Number
- CN202511681891.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-17
- Publication Date
- 2026-02-06
AI Technical Summary
Existing NdFeB permanent magnet materials have higher requirements for corrosion resistance, temperature stability and coercivity in fields such as new energy vehicles and wind power generation, and the consumption of rare earth elements is increasing. The single component of the existing diffusion source leads to poor diffusion effect, making it difficult to produce on a large scale in industry.
A mixed grain boundary diffusion source, consisting of TbHx powder and Pr70Al20Cu10 alloy powder, with the addition of polyvinylpyrrolidone, polyurethane and alumina, is used to form a uniform coating on the surface of NdFeB magnets through screen printing and heat treatment. Pressure is then applied to induce diffusion and optimize the distribution of grain boundary phases.
It improves the coercivity and diffusion efficiency of NdFeB magnets, simplifies the production process, reduces the amount of rare earth elements used, and enhances the utilization rate and diffusion effect of the diffusion source.
Smart Images

Figure CN121483855A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of grain boundary diffusion process for sintered NdFeB permanent magnet materials, and particularly relates to a mixed grain boundary diffusion source for sintered NdFeB magnets, its preparation method and application. Background Technology
[0002] Sintered NdFeB permanent magnets have the highest energy density among all permanent magnets. Their raw materials are also more abundant and relatively cheaper, making them more conducive to sustainable development. Currently, NdFeB permanent magnet materials are widely used in new energy vehicles, machinery manufacturing, computers, petrochemicals, microwave communications, the automotive industry, bioengineering, instrumentation technology, electrical engineering, transportation, electroacoustic equipment, medical devices, industry and agriculture, and national defense technology.
[0003] The increasing demand for NdFeB permanent magnet materials brings both development opportunities and significant challenges to the industry. Applications such as new energy vehicles and wind power generation place higher demands on the corrosion resistance, temperature stability, and coercivity of NdFeB permanent magnet materials. Furthermore, with the continuous growth in demand for NdFeB magnets, the consumption of rare earth elements such as Pr, Nd, Dy, and Tb is also gradually increasing. Insufficient reserves of heavy rare earth elements, rising prices, and reduced product cost-effectiveness are also important factors restricting the development of the NdFeB industry.
[0004] Grain boundary diffusion technology is a hot research area in NdFeB-related fields. Its aim is to optimize the coercivity of magnets while minimizing the amount of rare earth elements used, reducing remanence loss, improving rare earth element utilization, and lowering production costs. In existing technologies, diffusion sources are mostly single-component, such as rare earth fluorides, rare earth hydrides, and low-melting-point alloys, resulting in relatively simple diffusion mechanisms and poor diffusion effects. Chinese patent CN 117410091 A discloses a grain boundary diffusion process for NdFeB magnets, which involves coating the surface of a NdFeB blank with a slurry of heavy rare earth elements and subjecting it to vibration treatment, causing the heavy rare earth powder in the slurry to deposit onto the surface of the NdFeB blank. While this process is simple and easy to implement, and helps reduce the carbon and oxygen content on the sample surface, it is difficult to reduce the impurity content within the entire magnet material and cannot effectively improve the uniformity of the internal grain boundary phase, thus making it difficult to improve the diffusion efficiency of the diffusion source within the matrix. Meanwhile, some studies have also explored the preparation of a double-layer coating on the surface of magnets for two-step grain boundary diffusion. However, this method has low diffusion source utilization and a relatively complicated production process, which is not conducive to large-scale industrial production.
[0005] Therefore, researching a hybrid diffusion source to improve grain boundary diffusion efficiency and simplify the diffusion process through multi-component synergistic diffusion has become an urgent problem to be solved. Summary of the Invention
[0006] The technical problem to be solved by the present invention is to provide a mixed grain boundary diffusion source for sintered NdFeB magnets, its preparation method and application, so as to solve the problems mentioned in the background art or achieve better technical effects.
[0007] To solve the above-mentioned technical problems, the inventors, through practice and summarization, derived the technical solution of this invention. This invention discloses a mixed grain boundary diffusion source for sintered NdFeB magnets, wherein the amount of each component, by weight, is: 70~93 parts TbH x Powder, 24-47 parts Pr 70 Al 20 Cu 10 Alloy powder, 43 parts ethanol, 5 parts polyvinylpyrrolidone, 1 part alumina and 1 part polyurethane;
[0008] The TbH x Powder and the Pr 70 Al 20 Cu 10 The particle size of the alloy powder is 3~5μm.
[0009] Furthermore, the amount of each component, by weight, is: 82 parts TbH x Powder, 35 parts Pr 70 Al 20 Cu 10 Alloy powder, 43 parts ethanol, 5 parts polyvinylpyrrolidone, 1 part alumina and 1 part polyurethane.
[0010] Furthermore, the preparation method of any of the above-described sintered NdFeB magnets using a mixed grain boundary diffusion source comprises the following steps:
[0011] S1: A 10 wt.% polyvinylpyrrolidone alcohol solution was prepared by mixing polyvinylpyrrolidone with alcohol and used as a solvent for the diffusion source slurry;
[0012] S2: Slowly add the polyurethane to the polyvinylpyrrolidone alcohol solution in S1 while stirring until the polyurethane is completely dissolved in the polyvinylpyrrolidone alcohol solution to form a homogeneous mixture.
[0013] S3: Add alumina powder to the mixture in S2, and after initial stirring, add TbHx powder and Pr... 70 Al 20 Cu 10 Alloy powders are mixed in proportion and then slowly added. After stirring until the powders are uniformly dissolved in the mixture, a mixed grain boundary diffusion source slurry is obtained.
[0014] Furthermore, in the entire mixed grain boundary diffusion source slurry system, the added polyvinylpyrrolidone can effectively disperse TbH. x Powder and Pr70 Al 20 Cu 10 Alloy powders should be used to prevent aggregation or stratification.
[0015] Furthermore, the addition of polyurethane to the entire hybrid diffusion source slurry system can significantly improve the viscosity and thixotropy of the slurry, ensuring the uniformity and stability of the diffusion source coating, reducing the surface tension of the slurry system, promoting the wetting and dispersion of the powder, and mitigating the TbH content in the slurry. x Powder and Pr 70 Al 20 Cu 10 The layering phenomenon caused by density differences in alloy powder improves the uniformity and consistency of the diffusion coating.
[0016] Furthermore, in the dispersion of TbH x Powder and Pr 70 Al 20 Cu 10 Before alloy powder is applied, introducing alumina powder into the mixture can prevent the magnets from sticking together during the subsequent pressurized heat treatment process.
[0017] Furthermore, the application of any of the aforementioned sintered NdFeB magnets using a mixed grain boundary diffusion source in the NdFeB magnet grain boundary diffusion process.
[0018] Furthermore, the application of the mixed grain boundary diffusion source for sintered NdFeB magnets in the grain boundary diffusion process of NdFeB magnets is as follows: the prepared mixed grain boundary diffusion source is coated on the surface of the substrate to form a uniform coating. The diffusion source is dried to ensure a tight bond between the diffusion source and the substrate. Several groups of coated substrates are stacked. The contact ability between the substrates is adjusted by applying pressure. The coated substrates are heat-treated by tempering and nitrogen quenching until the grain boundary diffusion process of the sintered NdFeB magnets is completed.
[0019] Furthermore, the substrate is an N38 sintered NdFeB magnet, which is prepared using conventional powder metallurgy technology. The sintered billet is wire-cut to a size of 42.5mm*10mm*2mm. The cut sheets are acid-washed in a 3wt.% dilute nitric acid solution for 30s, ultrasonically cleaned in alcohol for 5min, and then dried for later use.
[0020] Furthermore, the diffusion source is printed on the surface of the magnet using screen printing, with the screen having a mesh size of 200.
[0021] Furthermore, after drying, the coating content accounts for 0.8~1.2 wt.% of the magnet.
[0022] Furthermore, the tempering process employs a two-stage tempering process with temperatures of 900℃ and 400℃ respectively.
[0023] Furthermore, the application of the mixed grain boundary diffusion source for sintered NdFeB magnets in the grain boundary diffusion process of NdFeB magnets includes the following steps:
[0024] S1: Sintered NdFeB magnet of N38 is selected as the diffusion matrix, and its chemical composition is (Nd, Pr). 20.4 Ce 11.7 B 0.9 8Al 0.1 Co 0.1 Zr 0.36 Cu 0.15 Fe 66.21 (wt.%), the magnets are produced using traditional powder metallurgy processes. The specific production process includes: batching, smelting, rapid solidification casting, hydrogen crushing, air jet milling, orientation pressing and sintering heat treatment. The sintered billet is wire-cut to a size of 42.5mm*10mm*2mm. The cut sheets are acid-washed in a 3wt.% dilute nitric acid solution for 30s, then ultrasonically cleaned in alcohol for 5min and dried for later use.
[0025] S2: The diffusion source paste is uniformly printed onto the magnet surface through a 200-mesh screen. After the coating is prepared, the magnet is placed in an oven at 130℃ for 15 minutes to dry it, making the bonding between the diffusion source and the magnet tighter and improving the diffusion effect and efficiency. After drying, the mass fraction of the coating is 0.8~1.2 wt.% of the magnet.
[0026] S3: Magnets with a size of 42.5mm*10mm*2mm and diffusion coating on the upper and lower surfaces are vertically stacked in a graphite box with a height of 60mm*90*180mm. The top and bottom pieces are calcined pieces. Finally, a graphite block with a length of 42.5mm, a width of 10mm, and a height of 30mm is placed on top of the stacked magnets to apply pressure between the magnets. The pressure between the magnets can be adjusted by changing the weight of the graphite block.
[0027] S4: The printed magnets are heat-treated using a two-stage tempering process at 900℃+480℃. The tempered magnets are then quenched by purging nitrogen gas to complete the grain boundary diffusion process of the sintered NdFeB magnets and optimize the coercivity of the magnets.
[0028] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0029] (1) This invention uses Pr 70 Al 20 Cu 10A diffusion source prepared by mixing alloy powder and TbHx powder in a certain proportion can better utilize Pr 70 Al 20 Cu 10 In alloy powder, Al and Cu elements wet the grain boundary phase, making the grain boundary phase distribution more uniform and playing a better auxiliary diffusion effect. In TbHx powder, the heavy rare earth element Tb enhances the coercivity of the magnet by generating a "shell structure" with higher magnetocrystalline anisotropy around the main phase grains.
[0030] (2) In the process of preparing the mixed slurry system, the present invention adds polyvinylpyrrolidone, polyurethane and alumina powder to the solvent respectively. Polyvinylpyrrolidone and polyurethane can improve the uniformity and consistency of the diffusion source slurry and coating, and avoid stratification due to differences in powder density; while alumina can prevent the adhesion between adjacent magnets during pressure diffusion heat treatment.
[0031] (3) In the grain boundary diffusion process, the present invention stacks magnets vertically and presses them to apply pressure between the magnets, thereby increasing the contact ability between the magnets, improving the vacuum between the magnets, reducing the oxidation of the magnets, improving the diffusion efficiency, and improving the diffusion effect.
[0032] (4) This diffusion method can simplify the traditional two-step diffusion production process and increase the utilization efficiency and diffusion effect of the diffusion source. Attached Figure Description
[0033] Figure 1 This is a schematic diagram of the coercivity increment in Embodiments 1-3 and Comparative Examples 1-3 of the present invention;
[0034] Figure 2 This is a scanning electron microscope image of the magnet at a distance of 500 μm from the surface, obtained in Example 1 of the present invention;
[0035] Figure 3 This is a scanning electron microscope image of the magnet at a distance of 500 μm from the surface, obtained in Comparative Example 1 of this invention;
[0036] Figure 4 This is a scanning electron microscope image of the magnet at a distance of 500 μm from the surface obtained in Comparative Example 2 of this invention;
[0037] Figure 5 This is a scanning electron microscope image of the magnet prepared in Comparative Example 3 of the present invention at a distance of 500 μm from the surface. Detailed Implementation
[0038] To make the above-mentioned objectives, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to specific examples.
[0039] Unless otherwise specified, the raw materials or reagents used in the following examples and comparative examples are commercially available products or products prepared using conventional techniques.
[0040] Among them, Pr 70 Al 20 Cu 10 The preparation method of the alloy powder is as follows: Traditional powder metallurgy processes are employed: batching, rapid solidification casting, hydrogen crushing, and air jet milling; Pr 70 Al 20 Cu 10 The particle size range of the alloy powder is 3~5μm.
[0041] TbH x The raw material for the diffusion source is pure metal Tb shavings, which does not require batching or rapid solidification into thin strips. The specific production process includes hydrogen crushing and air jet milling. The particle size range of the prepared diffusion source alloy powder is 3~5μm.
[0042] Example 1
[0043] A grain boundary diffusion slurry for sintered NdFeB magnets, comprising the following components by weight:
[0044] 82 TbH x Powder, 35 parts Pr 70 Al 20 Cu 10 Alloy powder, 43 parts ethanol, 5 parts polyvinylpyrrolidone, 1 part alumina, 1 part polyethylene ester;
[0045] The preparation method of the above-mentioned grain boundary diffusion slurry includes the following steps:
[0046] (1) A 10 wt.% polyvinylpyrrolidone alcohol solution was prepared by mixing polyvinylpyrrolidone with alcohol and used as a solvent for the diffusion source slurry;
[0047] (2) Slowly add polyurethane to the polyvinylpyrrolidone alcohol solution while stirring clockwise until the polyurethane is completely dissolved in the polyvinylpyrrolidone alcohol solution to form a homogeneous solution.
[0048] (3) Add alumina powder to the solvent and stir evenly. During the heat treatment process, the alumina powder is used to prevent the magnets from sticking together.
[0049] (4) TbH x Powder and Pr 70 Al 20 Cu 10 The alloy powder is mixed in a certain proportion and then slowly added to the solvent while stirring until the alloy powder is uniformly dissolved in the solvent, thus obtaining the diffusion source slurry.
[0050] Example 2
[0051] A grain boundary diffusion slurry for sintered NdFeB magnets, comprising the following components by weight:
[0052] 70 TbH x Powder, 47 parts Pr 70 Al 20 Cu 10 Alloy powder, 43 parts ethanol, 5 parts polyvinylpyrrolidone, 1 part alumina, 1 part polyethylene ester;
[0053] The preparation method of the above grain boundary diffusion slurry is the same as that in Example 1.
[0054] Example 3
[0055] A grain boundary diffusion slurry for sintered NdFeB magnets, comprising the following components by weight:
[0056] 93 TbH x Powder, 24 parts Pr 70 Al 20 Cu 10 Alloy powder, 43 parts ethanol, 5 parts polyvinylpyrrolidone, 1 part alumina, 1 part polyethylene ester;
[0057] The preparation method of the above grain boundary diffusion slurry is the same as that in Example 1.
[0058] Comparative Example 1
[0059] A grain boundary diffusion slurry for sintered NdFeB magnets, comprising the following components by weight:
[0060] 117 TbH x Powder, 43 parts ethanol, 5 parts polyvinylpyrrolidone, 1 part alumina, 1 part polyethylene ester;
[0061] The preparation method of the above grain boundary diffusion slurry is the same as that in Example 1.
[0062] Comparative Example 2
[0063] A grain boundary diffusion slurry for sintered NdFeB magnets, comprising the following components by weight:
[0064] 58.5 TbH x Powder, 58.5 parts Pr 70 Al 20 Cu 10 Alloy powder, 43 parts ethanol, 5 parts polyvinylpyrrolidone, 1 part alumina, 1 part polyethylene ester;
[0065] The preparation method of the above grain boundary diffusion slurry is the same as that in Example 1.
[0066] Comparative Example 3
[0067] A grain boundary diffusion slurry for sintered NdFeB magnets, comprising the following components by weight:
[0068] 117 Pr 70 Al 20 Cu 10 Alloy powder, 43 parts ethanol, 5 parts polyvinylpyrrolidone, 1 part alumina, 1 part polyethylene ester;
[0069] The preparation method of the above grain boundary diffusion slurry is the same as that in Example 1.
[0070] Example 4
[0071] The diffusion source slurries prepared in Examples 1-3 and Comparative Examples 1-3 were used to treat the sintered NdFeB magnet matrix using a grain boundary diffusion process to prepare NdFeB magnets. The method is as follows:
[0072] (1) Commercial grade N38 sintered NdFeB magnet was selected as the diffusion matrix, and its chemical composition is: (Nd, Pr) 20.4 Ce 11.7 B 0.98 Al 0.1 Co 0.1 Zr 0.36 Cu 0.15 Fe 66.21 (wt.%). The magnets are produced using traditional powder metallurgy processes, including: batching, smelting, rapid solidification casting, hydrogen annealing, air jet milling, orientation pressing, and sintering heat treatment. The sintered billets are wire-cut to dimensions of 42.5mm*10mm*2mm. The cut sheets are then acid-washed in a 3wt.% dilute nitric acid solution for 30 seconds, ultrasonically cleaned in alcohol for 5 minutes, and then dried for later use.
[0073] (2) The diffusion source is printed on the magnet surface by screen printing. The diffusion source pastes prepared in Examples 1-3 and Comparative Examples 1-3 are uniformly printed on the magnet surface through a 200-mesh screen. After the coating is prepared, the magnet is placed in an oven at 130°C for 15 minutes to make the diffusion source and the magnet more tightly bonded, thereby improving the diffusion effect and efficiency. The mass fraction of the coating after drying is 0.8-1.2 wt.% of the magnet.
[0074] (3) The magnets with a size of 42.5mm*10mm*2mm and a diffusion coating on the upper and lower surfaces are vertically stacked in the height direction into a graphite box of 60mm*90*180mm. The top and bottom pieces are calcined pieces. Finally, a graphite block with a length of 42.5mm, a width of 10mm and a height of 30mm is placed on top of the stacked magnets to apply pressure between the magnets. The pressure between the magnets can be adjusted by changing the weight of the graphite block.
[0075] (4) The printed magnet was heat-treated by a three-stage tempering process of 900℃+600℃+400℃. The tempered magnet was then quenched by purging nitrogen gas to complete the grain boundary diffusion process of the sintered NdFeB magnet and the optimization of the magnet coercivity.
[0076] Comparative Example 4
[0077] The diffusion source slurry prepared in Example 1 above was used to treat the sintered NdFeB magnet matrix using a grain boundary diffusion process to prepare NdFeB magnets, as follows:
[0078] (1) Same as step (1) in Example 4;
[0079] (2) The diffusion source was printed onto the magnet surface using screen printing. The diffusion source paste prepared in Example 1 was uniformly printed onto the magnet surface through a 200-mesh screen. After the coating was prepared, the magnet was placed in an oven and dried at 130°C for 15 minutes to make the diffusion source and the magnet more tightly bonded, thereby improving the diffusion effect and efficiency. After drying, the mass fraction of the coating was 0.8-1.2 wt.% of the magnet.
[0080] (3) Place the magnets with a size of 42.5mm*10mm*2mm and diffusion coating on the upper and lower surfaces into a graphite box with a size of 60mm*90*180mm in a horizontal stack, without applying pressure above the magnets;
[0081] (4) is the same as step (4) in Example 4.
[0082] The room temperature demagnetization curve, coercivity (Hcj), remanence (Br), and maximum energy product ((BH)max) of the magnet were measured using a PFM ultra-high coercivity permanent magnet measuring instrument. The test results are shown in Table 1 below:
[0083] Table 1. Comparison of test results between the prepared NdFeB magnets and the N38 substrate.
[0084]
[0085] For Table 1 and Figure 1Analysis shows that, comparing Examples 1-3 with Comparative Examples 1-3, when the TbH in the diffusion source slurry... x Powder and Pr 70 Al 20 Cu 10 When the alloy powder content is 70-93 parts and 24-47 parts, the coercivity of the sintered NdFeB magnet is significantly improved, reaching 3.92-5.37 kOe.
[0086] A comparison of Example 1 and Comparative Example 1 reveals that when Pr was not added to the slurry... 70 Al 20 Cu 10 When using alloy powder, the increase in coercivity is not significant because Pr... 70 Al 20 Cu 10 Al and Cu elements in the alloy powder will enter the Nd-rich phase at the grain boundaries, improving the wetting angle between the grain boundary phase and the main phase grains, making the distribution of the grain boundary phase more uniform, and assisting TbH x The Tb element in the powder diffuses along the grain boundary phase into the magnet, increasing the diffusion depth and optimizing the diffusion effect. Figure 2 and Figure 3 It can be seen that the distribution of grain boundary phase inside the magnet in Example 1 is more uniform, and the diffusion effect is better.
[0087] A comparison of Example 1 and Comparative Example 2 reveals that when TbH was not added to the slurry... x When powdered, the increase in coercivity is significantly reduced. This is because during grain boundary diffusion, Tb elements diffuse along the magnet grain boundary phase toward the interior of the magnet, and under the drive of the concentration gradient, diffuse toward the main phase grains, replacing Nd2Fe. 14 Nd elements on the surface of the B main phase grains generate Dy2Fe with higher magnetocrystalline anisotropy. 14 The B phase generates a "core-shell structure" to improve the intrinsic magnetic properties of the magnet and optimize its coercivity. Figure 2 and Figure 4 It can be seen that the distribution of grain boundary phase inside the magnet in Example 1 is more uniform, and the diffusion effect is better.
[0088] A comparison of Example 1 and Comparative Example 3 reveals that when Pr is added to the slurry... 70 Al 20 Cu 10 Alloy powder and TbH x When the powder ratio is outside the range of the examples, the coercivity increment decreases because of the Pr in the examples. 70 Al 20 Cu 10 Alloy powder and TbH x The powder ratio is within the optimal range to better utilize Pr70 Al 20 Cu 10 Alloy powder-assisted diffusion effect and TbH x The addition of Tb element in the powder enhances the magnet's magnetocrystalline anisotropy, thereby improving the magnet's coercivity. When Pr in the slurry... 70 Al 20 Cu 10 When the proportion of alloy powder is lower than that in the examples, the auxiliary diffusion effect is limited, the uniformity of grain boundary phase distribution decreases, the diffusion depth decreases, and the coercivity increment decreases; when the TbH content in the slurry is lower... x When the proportion of powder is lower than the range of the examples, the content of the heavy rare earth element Tb diffused into the magnet decreases, making it impossible to effectively generate a "core-shell structure" with higher magnetic anisotropy on the surface of the main phase grains of the magnet to improve the magnet's coercivity, resulting in a decrease in the coercivity increment. Figure 2 and Figure 5 It can be seen that the distribution of grain boundary phase inside the magnet in Example 1 is more uniform, and the diffusion effect is better.
[0089] A comparison of the slurry from Example 1 processed by the grain boundary diffusion process of Example 4 with that of Comparative Example 4 reveals that when magnets are not stacked vertically in the height direction and a graphite block is placed on top to apply pressure between the magnets, but instead are loaded using a horizontal stacking method, the coercivity increment of the magnets will also decrease. This is because horizontal stacking cannot create sufficient pressure between the magnets, resulting in a decrease in the contact ability between the magnets, a decrease in the vacuum between the magnets, an increase in the degree of oxidation, a decrease in diffusion efficiency, and a decrease in the diffusion effect.
[0090] This invention is the first to adjust the TbH content in the diffusion source slurry. x Powder and Pr 70 Al 20 Cu 10 The proportions of the alloy powder can be determined using TbH. x Powder and Pr 70 Al 20 Cu 10 The synergistic mechanism of alloy powder effectively enhances the coercivity and optimizes the magnetic properties of sintered NdFeB magnets through grain boundary diffusion process; and during the grain boundary diffusion process, pressure is applied between the magnet printing interfaces to enhance the contact ability between different magnets, thereby improving diffusion efficiency and utilization of diffusion source.
Claims
1. A mixed grain boundary diffusion source for sintered NdFeB magnets, characterized in that, The dosage of each component, by weight, is 70-93 parts TbH. x Powder, 24-47 parts Pr 70 Al 20 Cu 10 Alloy powder, 43 parts ethanol, 5 parts polyvinylpyrrolidone, 1 part alumina and 1 part polyurethane; The TbH x Powder and the Pr 70 Al 20 Cu 10 The particle size of the alloy powder is 3~5μm.
2. The mixed grain boundary diffusion source for sintered NdFeB magnets according to claim 1, characterized in that, The amount of each component, by weight, is: 82 parts TbH x Powder, 35 parts Pr 70 Al 20 Cu 10 Alloy powder, 43 parts ethanol, 5 parts polyvinylpyrrolidone, 1 part alumina and 1 part polyurethane.
3. A method for preparing a mixed grain boundary diffusion source for sintered NdFeB magnets as described in claim 1 or 2, characterized in that, The steps are as follows: S1: A 10 wt.% polyvinylpyrrolidone alcohol solution was prepared by mixing polyvinylpyrrolidone with alcohol and used as a solvent for the diffusion source slurry; S2: Slowly add the polyurethane to the polyvinylpyrrolidone alcohol solution in S1 while stirring until the polyurethane is completely dissolved in the polyvinylpyrrolidone alcohol solution to form a homogeneous mixture. S3: Add alumina powder to the mixture in S2, and after initial stirring, add TbH... x Powder and Pr 70 Al 20 Cu 10 Alloy powders are mixed in proportion and then slowly added. After stirring until the powders are uniformly dissolved in the mixture, a mixed grain boundary diffusion source slurry is obtained.
4. The application of the mixed grain boundary diffusion source for sintered NdFeB magnets as described in claim 1 or 2 in the grain boundary diffusion process of NdFeB magnets.
5. The application of the mixed grain boundary diffusion source for sintered NdFeB magnets according to claim 4 in the grain boundary diffusion process of NdFeB magnets, characterized in that, The method is as follows: the prepared mixed grain boundary diffusion source is coated on the surface of the substrate to form a uniform coating. The diffusion source is dried to make it bond tightly with the substrate. Several groups of coated substrates are stacked. The contact ability between the substrates is adjusted by applying pressure. The coated substrates are heat-treated by tempering and nitrogen quenching until the grain boundary diffusion process of the sintered NdFeB magnet is completed.
6. The application of the mixed grain boundary diffusion source for sintered NdFeB magnets according to claim 5 in the grain boundary diffusion process of NdFeB magnets, characterized in that, The substrate is an N38 sintered NdFeB magnet, which is prepared using conventional powder metallurgy. The sintered billet is wire-cut to a size of 42.5mm*10mm*2mm. The cut sheets are acid-washed in a 3wt.% dilute nitric acid solution for 30s, ultrasonically cleaned in alcohol for 5min, and then dried for later use.
7. The application of the mixed grain boundary diffusion source for sintered NdFeB magnets according to claim 5 in the grain boundary diffusion process of NdFeB magnets, characterized in that, The diffusion source is printed on the surface of the magnet using screen printing, with the screen having a mesh size of 200.
8. The application of the mixed grain boundary diffusion source for sintered NdFeB magnets according to claim 5 in the grain boundary diffusion process of NdFeB magnets, characterized in that, After drying, the coating content accounts for 0.8~1.2 wt.% of the magnet.
9. The application of the mixed grain boundary diffusion source for sintered NdFeB magnets according to claim 5 in the grain boundary diffusion process of NdFeB magnets, characterized in that, The tempering process adopts a two-stage tempering process with temperatures of 900℃ and 400℃ respectively.
10. The application of the mixed grain boundary diffusion source for sintered NdFeB magnets according to any one of claims 5 to 9 in the grain boundary diffusion process of NdFeB magnets, characterized in that, The steps are as follows: S1: Sintered NdFeB magnet of N38 is selected as the diffusion matrix, and its chemical composition is (Nd, Pr). 20.4 Ce 11.7 B 0.98 Al 0. 1Co 0.1 Zr 0.36 Cu 0.15 Fe 66.21 (wt.%), the magnets are produced using traditional powder metallurgy processes. The specific production process includes: batching, smelting, rapid solidification casting, hydrogen crushing, air jet milling, orientation pressing and sintering heat treatment. The sintered billet is wire-cut to a size of 42.5mm*10mm*2mm. The cut sheets are acid-washed in a 3wt.% dilute nitric acid solution for 30s, then ultrasonically cleaned in alcohol for 5min and dried for later use. S2: The diffusion source paste is uniformly printed onto the magnet surface through a 200-mesh screen. After the coating is prepared, the magnet is placed in an oven at 130℃ for 15 minutes to dry it, making the bonding between the diffusion source and the magnet tighter and improving the diffusion effect and efficiency. After drying, the mass fraction of the coating is 0.8~1.2 wt.% of the magnet. S3: Magnets with a size of 42.5mm*10mm*2mm and diffusion coating on the upper and lower surfaces are vertically stacked in a graphite box with a height of 60mm*90*180mm. The top and bottom pieces are calcined pieces. Finally, a graphite block with a length of 42.5mm, a width of 10mm, and a height of 30mm is placed on top of the stacked magnets to apply pressure between the magnets. The pressure between the magnets can be adjusted by changing the weight of the graphite block. S4: The printed magnets are heat-treated using a two-stage tempering process at 900℃+480℃. The tempered magnets are then quenched by purging nitrogen gas to complete the grain boundary diffusion process of the sintered NdFeB magnets and optimize the coercivity of the magnets.
Citation Information
Patent Citations
Grain boundary diffusion process of neodymium-iron-boron magnet
CN117410091A